Magnesium materials : from mountain bikes to degradable bone grafts - Oshida, Yoshiki (De Gruyter, 2021)
The book provides an introduction to the topic of magnesium materials for biomedical applications. Additional to the background on magnesium's physical, chemical and mechanical properties, areas of use, related diseases and pathways for biodegradation will be discussed. Also, an outlook of the future of magnesium material applications will be provided.
Keywords: Magnesium.; Chemistry, Technical.; Biomedical engineering.; Magnesium -- Industrial applications.; elektronické knihy; electronic books